KEANEKARAGAMAN MAKROFAUNA TANAH PADA PERKEBUNAN KELAPA SAWIT DENGAN USIA BERBEDA - Juliarni, Juliarni; Rambe, Taufik Ristumoyo (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
One of the bioindicators of soil fertility is soil macrofauna. Macrofauna acts as a decomposer of organic matter so that it can increase nutrient distribution and improve the physical, chemical and biological properties of the soil. Soil macrofauna is also very sensitive to environmental changes. Changes in land use for oil palm commodity production areas are related to changes in soil biodiversity. This study aims to compare the diversity of soil macrofauna in oil palm plantations of different ages. This research was conducted by survey method and determining the location of research with the Purpossive Sampling method. Sample points were taken on the palm oil disc, live and interrow. Sampling was done using a box sampler, followed by a hand sorting method and identified to the family level. Macrofauna calculations are performed on the number of families, population density (KP), relative density (KR), Shannon-Wiener index (H ’) and evenness index (E’). Data obtained were analyzed statistically using a t-test at 5% level. The results showed that the average number of soil macrofauna families tended to be higher in 13 year old oil palms in interrow (GM), namely 12.83 ± 1.33. Eight families of soil macrofauna that have a higher population density and relative density than other families are Termitidae, Formicidae, Lumbricidae, Cylisticidae, Lithobiidae, Anisolabidiidae, Mecistocphalidae, and Geophilidae. The diversity index of soil macrofauna in 13 year old oil palms tends to be higher in the interrow (GM) area, namely 2.49 ± 0.18 (medium) compared to the others. The evenness index of soil macrofauna in 5 year and 13 year old oil palms was included in the high category (>0.5), namely 0.63-0.73.